1978
DOI: 10.1002/ijc.2910210210
|View full text |Cite
|
Sign up to set email alerts
|

In vitro measurement of carcinogen‐resistant liver cells during hepatocarcinogenesis

Abstract: Following the transfer of r a t liver cells from 2-acetylaminofluorene-induced, grey-white hyperplastic nodules t o a primary, monolayer cell culture system, the proportion of the nodule cells which were resistant t o the cytotoxic effects of aflatoxin B1 was determined normal and nodule hepatocytes were great following aflatoxin B1 treatment. Aflatoxin B1 treatment inhibited the spreading of normal hepatocytes, whereas the highly resistant nodule hepatocytes continued t o spread out on the plastic substratum.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

1981
1981
1987
1987

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…This phenotypic property is obvious both irz viw, when nodule-bearing animals arc treated with different toxic substances (32,89), and itt vitro by treating nodular cells in tissue culture (13,14,48). The biological significance of this tolerance to xenobiotic substances is not known in detail, but in the hepatocarcinogenic protocols where mitoinhibitory or other toxic drugs are used in the promotion phase, the resistance certainly seems to be important, permitting the selective proliferation of initiated cells to foci and hepatocyte nodules.…”
Section: Introductionmentioning
confidence: 99%
“…This phenotypic property is obvious both irz viw, when nodule-bearing animals arc treated with different toxic substances (32,89), and itt vitro by treating nodular cells in tissue culture (13,14,48). The biological significance of this tolerance to xenobiotic substances is not known in detail, but in the hepatocarcinogenic protocols where mitoinhibitory or other toxic drugs are used in the promotion phase, the resistance certainly seems to be important, permitting the selective proliferation of initiated cells to foci and hepatocyte nodules.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that HNs with similar morphologic and biochemical properties are produced following exposure of rats to any of a variety of different carcinogens (10)(11)(12)(13)(14)(15)(16). Moreover, these carcinogen-induced changes in HNs are associated with the development of resistance to many structurally diverse hepatotoxins (10)(11)(12)(13)(14)(15)(16), prompting Farber to use the term "resistant hepatocyte model" in describing this system (16). The induction of stable levels of an anionic GSHTase isoenzyme in HNs resistant to various hepatotoxins, and in DoxR cells resistant to many naturally occurring antineoplastic agents, prompted us to compare the biochemical changes in these two models in more detail.…”
mentioning
confidence: 99%
“…Chronic or recurrent necrosis of hepatic cells can result in regenerative stimuli and be a mechanism of tumor promotion (38). Hepatic cells initiated by DEN may also be resistant to the effects of cytotoxic chemicals such as 3,3',4,4',5,5'-HBB and have an increased responsiveness to endogenous or exogenous growth stimuli (39,40). It is our contention that it is important to distinguish between tumor promoters that can exert effects at noncytotoxic doses and those that can only promote as a secondary effect of hepatic necrosis.…”
mentioning
confidence: 99%